Association between thyroid function and metabolic associated fatty liver disease: a systemic review and meta-analysis - Xiong, Wei; Fan, Hua; Tang, Jiake; Yu, Qingwen; Xin, Ziyi; Tang, Ting; Rao, Xiyun; Feng, Lanlan; Shi, Yongmin; Tong, Xuhan; Fu, Xinyan; Zhang, Xingwei; et al. (Frontiers in Endocrinology, 2025)
BackgroundMetabolic dysfunction–associated fatty liver disease (MAFLD) is one of the most common chronic liver diseases. The relationship between MAFLD and thyroid function parameters remains controversial.AimThis study aimed to explore the influence of metabolic parameters and thyroid dysfunction on the development of MAFLD and examine the relationship between them in different age groups.MethodsThe PubMed, Embase, Web of Science, China National Knowledge Infrastructure(CNKI), and Cochrane Library databases were searched. Standardized mean difference (SMD) and odds ratio with a 95% confidence interval (CI) were calculated.ResultsA total of 36 studies involving 198,254 participants were eligible. Compared with controls, the patients with MAFLD had significantly higher thyroid-stimulating hormone (TSH) levels (MAFLD vs controls: SMD = 0.02, 95% CI = 0.01–0.03); significantly higher free triiodothyronine levels (MAFLD vs controls: SMD = 0.19, 95% CI = 0.18–0.20); significantly lower free thyroxine levels (MAFLD vs controls: SMD = −0.41, 95% CI = −0.42 to −0.40); significantly higher total triiodothyronine levels (MAFLD vs controls: SMD = 0.26, 95% CI = 0.23–0.29); and significantly lower total thyroxine levels (MAFLD vs controls: SMD = −0.10, 95% CI = −0.13 to −0.07).ConclusionsThe TSH level may be an important risk factor for the occurrence and development of MAFLD. The relationship between them is influenced by age.